2000
DOI: 10.1128/mcb.20.15.5516-5528.2000
|View full text |Cite
|
Sign up to set email alerts
|

Bop1 Is a Mouse WD40 Repeat Nucleolar Protein Involved in 28S and 5.8S rRNA Processing and 60S Ribosome Biogenesis

Abstract: We have identified and characterized a novel mouse protein, Bop1, which contains WD40 repeats and is highly conserved through evolution. bop1 is ubiquitously expressed in all mouse tissues examined and is upregulated during mid-G 1 in serum-stimulated fibroblasts. Immunofluorescence analysis shows that Bop1 is localized predominantly to the nucleolus. In sucrose density gradients, Bop1 from nuclear extracts cosediments with the 50S-80S ribonucleoprotein particles that contain the 32S rRNA precursor. RNase A tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
182
1
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 166 publications
(194 citation statements)
references
References 90 publications
6
182
1
5
Order By: Relevance
“…The analysis of the human nucleolus proteome recently demonstrated that GRWD, Pescadillo and Bop1 are present in the nucleolus, the cellular site of ribosome biogenesis (Scherl et al, 2002) and we confirmed the former localization of GRWD by immunocytochemistry. Furthermore, the involvement of Pescadillo and Bop1 in ribosome biogenesis has been documented clearly in mammalian cells (Strezoska et al, 2000;Lerch-Gaggl et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the human nucleolus proteome recently demonstrated that GRWD, Pescadillo and Bop1 are present in the nucleolus, the cellular site of ribosome biogenesis (Scherl et al, 2002) and we confirmed the former localization of GRWD by immunocytochemistry. Furthermore, the involvement of Pescadillo and Bop1 in ribosome biogenesis has been documented clearly in mammalian cells (Strezoska et al, 2000;Lerch-Gaggl et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the Drosophila screen the genes identified were largely ribosomal subunit genes, whereas our data also illustrate the roles of ribosome assembly factors, and tRNA synthesis, processing, and charging proteins in regulating G1. Given that down-regulation of ribosome biogenesis can cause cell cycle arrest in G1 in mouse and human cells (Strezoska et al, 2000;Volarevic et al, 2000;Pestov et al, 2001;Oliver et al, 2004), our identification of essential genes that regulate G1 in yeast could be useful in dissecting connections between ribosome biogenesis and cell cycle progression in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…3 H]methionine to take advantage of the rapid turnover of the cellular methionine pool (35). The cells were starved for 15 min in methionine-free medium and then incubated for 30 min in medium containing L-[methyl-…”
Section: Methodsmentioning
confidence: 99%